Udmurt Poetry of the late 20th and early 21st century: Transformation of Genres, Styles, and Images - Vera G. Panteleeva (Studia Litterarum)
The turn of the 20 th and 21 st centuries has fostered the emergence of poetic patterns that reveal mythopoetical traditions and genetic memory about the nation’s historical destiny as well as models that correspond with the current tendencies in Russian and European literature. The article mainly focuses on the poetry of M. Fedotov, E. Batuev, S. Matveev, Z, Riabinina, and A. Shumilova, poets who are different in their manner and style but have one feature in common: they all share the crisis mentality of their generation that effaced the dramatic turn-of-the-century collisions. New Udmurt poetry features laconic aesthetic forms and transformation of imagery and stylistic modality in poems. The ultimate use of means provided by phonetics and syntax of the language, and intentional transformation of stanza structure and punctuation represent the fundamental modification of modern versification. Poetic styles and symbols have become polysemantic, ironic, explicitly aggressive, and conspicuously colloquial. Modern Udmurt poetry requires a variety of research approaches and interpretations since it encloses traditional ethnic and cultural codes, the heritage of Russian, Finno- Ugric, and European literature, and the recent phenomena of the media culture.